STUDENTS’ PERCEPTION ON THE USED OF LIQUID CRYSTAL DISPLAY (LCD) PROJECTOR IN ENGLISH FOREIGN LANGUAGE (EFL) CLASSROOM - Idami, Zahratul (JL3T (Journal of Linguistics, Literature and Language Teaching), 2018)
In line with information and communication technology development, foreign-language teachers should prepare more exciting ways to enhance students’ motivation in learning foreign language. One of the innovative media is Liquid Crystal Display (LCD) projector. Thus this article aims to find out and to describe students’ perception on Liquid Crystal Display (LCD) projector in learning English Foreign Language (EFL). This research conducted for the second year students of SMA Negeri 1 Bireuen in academic year 2018/2019 with total population 331 students and 90 of them were the sample. This was a qualitative descriptive research, and questionnaire was used as the instrument to obtain the data. Moreover, the simple calculation of descriptive statistics was used in analyzing the data, such as mean and percentage. The result revealed that the availability of Liquid Crystal Display (LCD) projector in EFL classroom built a more conducive and vivid learning atmosphere, so the students’ motivation was also improved.